2012
DOI: 10.4236/eng.2012.410b014
|View full text |Cite
|
Sign up to set email alerts
|

Infra-red Thermal Imaging of the Inner Canthus: Correlates with the Temperature of the Injured Human Brain

Abstract: Introduction: Infra-red (IR) thermometry is a safe and valid method to determine internal and surface temperature in human subjects. Under conditions of brain damage (head injury or stroke) knowledge of changes in the temperature of intracranial tissue is justified because of the vulnerability of neurons to accelerated damage at temperatures at the upper end of the febrile range. Aim: To determine the temperature at the inner canthus (IC) of the eye as a potential surrogate for brain temperature. Methods: Inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The camera's emissivity was set to ε = 0.95 to accurately measure the temperature of the inner canthus of the radiant eyelid (T ic,eye ) on both sides (Figure 1), considering that the thinner skin, with a high-k thermal conductivity (k = 0.00009 Kcal/(s•N•C)) and lower fat content in this area [9], typically results in an emissivity value closer to 0.95. All images were taken with the camera at a minimum focus distance of 0.3 meters (0.984 feet) in the multispectral mode.…”
Section: Evaluation Of Btt • By Infrared Thermographymentioning
confidence: 99%
See 2 more Smart Citations
“…The camera's emissivity was set to ε = 0.95 to accurately measure the temperature of the inner canthus of the radiant eyelid (T ic,eye ) on both sides (Figure 1), considering that the thinner skin, with a high-k thermal conductivity (k = 0.00009 Kcal/(s•N•C)) and lower fat content in this area [9], typically results in an emissivity value closer to 0.95. All images were taken with the camera at a minimum focus distance of 0.3 meters (0.984 feet) in the multispectral mode.…”
Section: Evaluation Of Btt • By Infrared Thermographymentioning
confidence: 99%
“…the thinner skin, with a high-k thermal conductivity (k = 0.00009 Kcal/(s•N•C)) and lower fat content in this area [9], typically results in an emissivity value closer to 0.95. All images were taken with the camera at a minimum focus distance of 0.3 meters (0.984 feet) in the multispectral mode.…”
Section: Evaluation Of Btt • By Infrared Thermographymentioning
confidence: 99%
See 1 more Smart Citation
“…A piece of research, aiming to verify if the temperature obtained with IRT imaging at the IC of the eye was related to brain temperature taken invasively (Childs et al 2012), found strong correlations between the temperatures of both sites, the IC of the eye and of the brain. It also showed that in patients with a lesion in one side of the brain, that the corresponding side had elevated temperature at the respective IC of the eye.…”
Section: Introductionmentioning
confidence: 99%